Energetic neutral atom imaging of the lunar surface. Issue 7 (1st July 2013) - Vorburger, A.; Wurz, P.; Barabash, S.; Wieser, M.; Futaana, Y.; Lue, C.; Holmström, M.; Bhardwaj, A.; Dhanya, M. B.; Asamura, K.
Abstract : [1] Since the Moon is not shielded by a global magnetic field or by an atmosphere, solar wind plasma impinges onto the lunar surface almost unhindered. Until recently, it was assumed that almost all of the impinging solar wind ions are absorbed by the surface. However, recent Interstellar Boundary Explorer, Chandrayaan‐1, and Kaguya observations showed that the interaction process between the solar wind ions and the lunar surface is more complex than previously assumed. In contrast to previous assumptions, a large fraction of the impinging solar wind ions is backscattered as energetic neutral atoms. Using the complete Chandrayaan‐1 Energetic Neutral Analyzer data set, we compute a global solar wind reflection ratio of 0.16 ± 0.05 from the lunar surface. Since these backscattered neutral particles are not affected by any electric or magnetic fields, each particle's point of origin on the lunar surface can be determined in a straight‐forward manner allowing us to create energetic neutral atom maps of the lunar surface. The energetic neutral atom measurements recorded by the Chandrayaan‐1 Energetic Neutral Analyzer cover ∼89 % of the lunar surface, whereby the lunar farside is almost completely covered. We analyzed all available energetic neutral atom measurements recorded by the Chandrayaan‐1 Energetic Neutral Analyzer to create the first global energetic neutral hydrogen maps of the lunar surface. Key Points: From the Chandrayaan-1/CENA data we compute a global ENA albedo of 0.16+/-0.05 We present the first global energetic hydrogen map of the lunar surface The high energy ENA map correlates well with magnetic field surface maps